Farmer’s perception towards competency of extension agents in transfer of technology in granary areas, Malaysia - Sidek, Wani (2016)
Paddy production in Malaysia still in low quantity which is cannot totally feed the population of Malaysian. In order to fulfill the requirement of the populations, government needs to import extra rice from other countries like Thailand and Vietnam. Besides, MARDI also proposed few ways to improve the yield production of paddy. One of that is introducing technology of Rice Check whereas comprised of ten components. Thus, the propose of this research is to study the farmer’s perception towards competency of the extension agents in transferring technology based on Rice Check through three skills. The skills are planning, implementing and monitoring. The method used is by using questionnaire and data analysis. The respondents chosen were farmers which come from four different granary areas of Malaysia which are IADA KETARA, IADA Pulau Pinang, IADA Kerian and IADA Seberang Perak with 535 respondents using sampling method by Krejcie and Morgan (1970). The questionnaire consists of two components which is demographic profile of farmers and competency level of extension agents in planning, implementing and monitoring the farmers based on Rice Check technology. The data taken were analyzed by using Statistical Package for Social Science (SPSS) version 21. The system used to analyze the descriptive data, correlation coefficient and regression in purpose to see the strength of relationship between independent variable and dependent variable. Independent variable comprised of component in technology transfer based on Rice Check namely planning, implementing and monitoring while dependent variable is the work performance of extension agents. Results show that the extension agents highly competence in the transferring of technology process in planning, implementing and monitoring. While the correlation shows moderate positive correlation between the independent variable with dependent variable. All the skills are important in affecting the work performance of extension agents in granary areas of Malaysia.